2009
DOI: 10.1158/1078-0432.ccr-09-1599
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Toll-Like Receptor 9 Agonist Cooperates with Trastuzumab in Trastuzumab-Resistant Breast Tumors through Multiple Mechanisms of Action

Abstract: Purpose: Resistance to anti-HER2 monoclonal antibody trastuzumab is a relevant issue in breast cancer patients. Among the mechanisms implicated in trastuzumab resistance, increasing evidence supports a role of tumor microenvironment. We previously found that a novel toll-like receptor 9 agonist, referred to as immune modulatory oligonucleotide (IMO) and currently under clinical investigation, acts through epidermal growth factor receptor (EGFR) and shows direct antiangiogenic effects by cooperating with anti-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 45 publications
5
34
0
Order By: Relevance
“…We have previously contributed to clarify some of these mechanisms showing that a TLR9 agonist, IMO, potentiates the ADCC activity of anti-EGFR mAb cetuximab (18) and anti-HER2 mAb trastuzumab (19) in in vivo models of colorectal and breast cancers, respectively. In addition to this immunomodulating function, we showed that IMO acts also by impairing EGFR signaling and potently synergizes in vivo both with cetuximab or EGFR TKI gefitinib in EGFR-addicted colorectal cancer models (20).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously contributed to clarify some of these mechanisms showing that a TLR9 agonist, IMO, potentiates the ADCC activity of anti-EGFR mAb cetuximab (18) and anti-HER2 mAb trastuzumab (19) in in vivo models of colorectal and breast cancers, respectively. In addition to this immunomodulating function, we showed that IMO acts also by impairing EGFR signaling and potently synergizes in vivo both with cetuximab or EGFR TKI gefitinib in EGFR-addicted colorectal cancer models (20).…”
Section: Introductionmentioning
confidence: 99%
“…The novel Toll-like receptor 9 (TLR9) agonist termed IMO, immune modulatory oligonucleotide, potentiates the anti-EGFR/HER2 signaling of monoclonal trastuzumab. It modulates a functional interaction between TLR9 and HER receptors at a membrane level, producing a cooperative antiangiogenic effect (Damiano et al, 2009). …”
Section: Toll-like Receptor Signaling In Tumor Angiogenesismentioning
confidence: 99%
“…Nevertheless, Grote et al and others (Chang et al, 2005;Spaner & Masellis, 2007;Damiano et al, 2009) suggest that future modulation of TLR signaling could be the basis for a therapeutic approach to cancer and inhibition or control of abnormal angiogenesis to limit tumor growth. However, this is potentially difficult because not only are there TLR-induced pro-angiogenic signals but also anti-angiogenic signals.…”
Section: Toll-like Receptor Signaling In Tumor Angiogenesismentioning
confidence: 99%
“…Attenuation of FoxM1 expression either by small interfering RNA or by an alternate reading frame (ARF)-derived peptide inhibitor increased the sensitivity to trastuzumab (Carr et al, 2010). Damiano et al report that a novel toll-like receptor 9 agonist, which is also referred as the immune modulatory oligonucleotide (IMO), exerts antiangiogenic effects by cooperating with anti-EGFR or anti-VEGF antobodies, (Damiano et al, 2009). It was also shown that IMO and trastuzumab exert a cooperative antiangiogenic effect on trastuzumab-resistant breast cancer xenografts and that combining IMO and trastuzumab may be a potential strategy for the treatment of trastuzumab-resistant breast cancers (Damiano et al, 2009).…”
Section: Development Of Novel Therapeutic Approaches: Mechanisms Of Rmentioning
confidence: 99%
“…Damiano et al report that a novel toll-like receptor 9 agonist, which is also referred as the immune modulatory oligonucleotide (IMO), exerts antiangiogenic effects by cooperating with anti-EGFR or anti-VEGF antobodies, (Damiano et al, 2009). It was also shown that IMO and trastuzumab exert a cooperative antiangiogenic effect on trastuzumab-resistant breast cancer xenografts and that combining IMO and trastuzumab may be a potential strategy for the treatment of trastuzumab-resistant breast cancers (Damiano et al, 2009). The Y-box binding protein-1 (YB-1) is an oncogenic transcription/translation factor mediating expression of growth promoting genes such as EGFR and HER2.…”
Section: Development Of Novel Therapeutic Approaches: Mechanisms Of Rmentioning
confidence: 99%